2020
DOI: 10.1007/978-3-030-60276-5_2
|View full text |Cite
|
Sign up to set email alerts
|

Hate Speech Detection Using Transformer Ensembles on the HASOC Dataset

Abstract: With the ubiquity and anonymity of the Internet, the spread of hate speech has been a growing concern for many years now. The language used for the purpose of dehumanizing, defaming or threatening individuals and marginalized groups not only threatens the mental health of its targets, as well as their democratic access to the Internet, but also the fabric of our society. Because of this, much effort has been devoted to manual moderation. The amount of data generated each day, particularly on social media platf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…Lastly, it is important to note here, that while in these experiments results attained with RoBERTa were not improved by the use of additional labeled training data, one can find opposing results in the literature. After the initial submission of this paper, Alonso et al [3] used 1 million tweets from the OffensEval training set to fine-tune the same RoBERTa model, then fine-tuned the resulting model further using the same five folds that we applied in our experiments, and Fig. 2 Hateful or offensive tweets where the hateful/offensive part is in Hindi found that the resulting ensemble performed better than the ensemble without fine-tuning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, it is important to note here, that while in these experiments results attained with RoBERTa were not improved by the use of additional labeled training data, one can find opposing results in the literature. After the initial submission of this paper, Alonso et al [3] used 1 million tweets from the OffensEval training set to fine-tune the same RoBERTa model, then fine-tuned the resulting model further using the same five folds that we applied in our experiments, and Fig. 2 Hateful or offensive tweets where the hateful/offensive part is in Hindi found that the resulting ensemble performed better than the ensemble without fine-tuning.…”
Section: Discussionmentioning
confidence: 99%
“…https ://paper swith code.com/task/text-class ifica tion 3. https ://paper swith code.com/task/senti ment-analy sis 4.…”
mentioning
confidence: 99%
“…Most of these approaches outperform traditional machine learning models. In addition, the recent advancements in language representation models such as ELMO [41], BERT [7], and XLM-R [9] have led to the considerable use of transformer-based pre-trained language models in hate speech and offensive language detection with competitive and promising results [42][43][44].…”
Section: A Hate Speech and Offensive Language Detectionmentioning
confidence: 99%
“…Fortuna and Nunes (2018) conducted a systematic review on automatic detection of hate speech in text and enumerated dictionary-based, rule-based, and feature-based techniques, as well as early deep learning models applied to this task. Since then, deep learning models, such as convolutional neural networks (CNN) (Gambäck & Sikdar, 2017), recurrent neural networks (RNN) (Zhang et al, 2018b), and transformers (Alonso et al, 2020), have been applied to build automatic abuse detection systems, and high performances have been achieved as these algorithms improved. Naseem et al (2020) showed that besides the training algorithms, preprocessing methods significantly impact the performance of the trained classifiers, which is often overlooked.…”
Section: Algorithmsmentioning
confidence: 99%